CGRP and Shh Mediate the Dental Pulp Cell Response to Neuron Stimulation. (August 2022) - Moore, E.R.; Michot, B.; Erdogan, O.; Ba, A.; Gibbs, J.L.; Yang, Y.
Dental pain is a persistent, detrimental public health issue that requires a better understanding of the mechanisms of tooth pain and inflammation in order to develop more effective treatments. Calcitonin gene-related peptide (CGRP) and dental pulp cells are promising candidates for mediating tooth pain and generating reparative dental tissues, respectively, but their behavior in the context of pulpitis remains elusive. The mouse incisor requires Sonic hedgehog (Shh) secreted from sensory nerves to continuously regenerate. However, it is unknown whether sensory nerves also regulate the comparatively nonregenerative mouse molar through CGRP and Shh. This is an important knowledge gap to fill since mouse incisors differ biologically from human teeth, while mouse and human molars are similar. In this work, we identified that molar pulp cells express CGRP receptor and Gli1, a Hedgehog (Hh) signaling protein found to label a dental stem cell population in the mouse incisor. We also observed in a mouse molar injury model that Hh signaling was activated and Shh expression was upregulated in vivo. We then determined in vitro that Shh and CGRP regulate differentiation of primary mouse molar and incisor pulp cells and a human dental pulp stem cell line. Furthermore, conditioned media from stimulated sensory neurons induced Hh signaling activation and inflammatory gene expression in primary molar pulp cells, which was abolished by inhibition of either Shh or CGRP. Our results suggest that CGRP and Shh signaling may promote an inflammatory response after injury in the molar and that activated sensory nerves secrete CGRP and Shh to regulate molar pulp cell expansion and differentiation into odontoblast-like cells for dentin repair. Thus, CGRP/Shh signaling should be considered for new strategies that seek to manage pain or dentin regeneration in the molar.